Considerations on the Representation of Women in Elite Research and Senior Administration Positions in Academe: An Interpretivist-Feminist Perspective - Dubuc, Tamar (Université d'Ottawa / University of Ottawa, 2021)
This dissertation examines the concept of underrepresentation as deployed in scholarly and gray literature to describe the paucity of women in elite research and senior administration positions in Canadian universities. I explore the meaning of underrepresentation, drawing from research in organization studies, feminist and gender studies, philosophy, and political studies, to discuss the different ideas and assumptions that converge to define the parameters of women’s underrepresentation. I demonstrate how underrepresentation arises as an unproblematized claim in gender and organization theorizing and holds significant implications for women in its partial and reductive descriptions. This dissertation proposes a conceptual revisioning based on views of representation that allows for a more holistic consideration of women in organizations—in the context of my research, women in elite research and senior administration positions in academe. I adopt a dual-study research design to determine the shape and measure of women’s representation from the field. Using thematic analysis (TA), I review institutional texts pertaining to the Canada Research Chairs program (CRCP) and transcripts from my interviews with women in senior administration roles in Canadian universities. My findings confirm the need to augment the conceptual framework to include views of representation in order to achieve greater alignment between gender and organization theorizing and women’s lived experiences. I conclude that views of representation hold the potential to disrupt the problematic claim of underrepresentation, thus allowing for a more holistic and multifaceted understanding of women in organizations. My dissertation is an interpretivist-feminist project that exposes a conceptual problematic for the purpose of producing and advancing theory that is critically constructive rather than critically reactive, rooted in women’s experiences, self-aware and committed to supporting social action in favour of women’s full participation and gender equity across all facets of academic organizational life.
Keywords: underrepresentation; representation; gender and organizations; gender and academe; women in administration; women in research; Canada Research Chairs program; gender equity